Jenis Laba-Laba Pada Tanaman Tomat (Lycopersicum esculentum Mill.) di Desa Ogomolos Kecamatan Mepanga - Dirham, Dirham; Noprianto, Carolus; Trianto, Manap (Universitas Tadulako, 2022)
Spiders are predatory arthropods found in agricultural areas that have an important role in maintaining the balance of the ecosystem. This study aims to determine the types of spiders found in tomato plants (Lycopersicum esculentum Mill.) in Ogomolos, Mepanga District, Central Sulawesi. This research was conducted from February to March 2018. The method used is a survey methods, by direct collection of spiders in the field using pitfall traps and also direct (hand sorting) on tomato plant. The number of spiders found consisted of 5 families and 2 orders and 5 species namely Lycosa pseudoannulata, Argiope catenulate, Tetragnatha montana, Oxyopes javanus and Heliophanus sp. The species most commonly found was Oxyopes javanus from the family Arachida.